Effect of Sacrificial Anodes on Hydrodynamic Coefficients of Jacket Members Subjected to Regular Waves - Raziqin, A. (EDP Sciences, 2017)
Designing a fixed offshore jacket platform requires the approximation of wave forces acting on jacket members which is influenced by multiple factors such as wave height, wave period, shape and size of the jacket member. An important part of determining wave forces using Morrison's equation is the accurate determination of hydrodynamic coefficients. The presence of sacrificial anodes increases the hydrodynamic coefficient of jacket member and therefore this research focuses on improving the design of fixed offshore platforms by conducting experimental investigation on rigid cylinders in order to obtaining better estimates for hydrodynamic coefficients. Steel members of size 27 and 34mm diameters were tested in the wave basin 20 m x 10 m x 1 m. Different set of regular waves with varying height and frequency were generated. Clean members were fitted with small welded steel bars of fixed length and size along the member simulating sacrificial anodes. The results show that the coefficients obtained were close to the values proposed by PTS and API standards but are generally lower than the suggested value of 2.0 for both Cd and Cm. © The Authors, published by EDP Sciences, 2017.